BANKING SYSTEMS IN ROMANIA AND ICELAND: TWO DIFFERENT WORLDS BUT SIMILAR DEVELOPMENT - Baicu, Claudia Gabriela; Mixa, Mar Wolfgang (Journal of Economic Development, Environment and People, 2017)
The novelty of this paper is the comparative analysis of the Romanian and Icelandic banking systems. The study results reveal that despite the fact that Romania and Iceland are two different worlds, there are several similarities between the banking systems of these countries. They include a late development of banking systems, foreigners contributing a great deal to the development of the banking systems in the early stage of evolution. After the Second World War until the 1990s specialized banks operated in both countries. The banking systems of both countries prior to the 1990s were dominated by politics. Liberalization of banking and capital occurred both in Romania and Iceland after 1990; the bank privatization process took place during a similar period (1999-2006, Romania; 1998-2002, Iceland). Before privatization, banks in both countries lacked experience in a new banking “arena”. The global financial crisis greatly affected the two banking systems. Despite similarities, the evolution of the two banking systems was also marked by differences, notably the ownership origin of banks after privatization (foreign dominance in Romania; domestic owners in Iceland) and different business models developed by banks in the pre-crisis period.